Scrierile lui Martin Luther din perspectiva polemicii - Daniel Nițulescu (TheoRhēma, 2018)
This article addresses the polemical aspect of Martin Luther’s controversial writings. Polemics, as well as dialectics, are as old as Antiquity, and have their origins in the disputes that were intended to find out the truth. It is interesting that the defenders of the Christian religion have found motivation for polemics in their desire to defend themselves. This is also true when it comes to one of the greatest Christian polemicists, Martin Luther. It is true that his controversial writings must be understood in the context of a Dark Middle Age. Lutheran polemics must be evaluated taking into account the two important stages of Luther’s work, namely, the Lutheran movement, until 1530, and the stage of institutionalization of the movement, after 1530. In the second phase, Luther had not only changed his language, but also the approach which caused him much frustration and dissatisfaction. However, for some of his non-conventional polemical manners we cannot find any excuse.